2020
DOI: 10.1136/bjsports-2020-102072
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Sport Concussion Assessment Tool 5 (SCAT5) in professional hockey, part 2: which components differentiate concussed and non-concussed players?

Abstract: ObjectivesTo examine the utility of Sport Concussion Assessment Tool (SCAT5) subcomponents in differentiating physician diagnosed concussed players from controls.MethodsWe evaluated 1924 professional hockey players at training camp using the National Hockey League (NHL) Modified SCAT5 prior to the 2018–2019 season. Over the course of the season, 314 English-speaking players received SCAT5 evaluations within 1 day of a suspected concussive event. Of these players, 140 (45%) were subsequently diagnosed with conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 26 publications
0
37
1
Order By: Relevance
“…A significantly higher number of symptoms and symptom severity has been reported in concussed professional hockey players compared to non-concussed players following a possible concussive incident, yet with median scores of 0 for both groups. 12 Commonly reported symptoms of headache, pressure in head, neck pain, and fatigue or low energy in concussed athletes were reported by both concussed and non-concussed athletes and therefore had lower diagnostic value. This finding is supported by other studies which have also found symptoms such as headache to be sensitive for concussion, however not specific if used in isolation without the assistance of other concussion assessment tools.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A significantly higher number of symptoms and symptom severity has been reported in concussed professional hockey players compared to non-concussed players following a possible concussive incident, yet with median scores of 0 for both groups. 12 Commonly reported symptoms of headache, pressure in head, neck pain, and fatigue or low energy in concussed athletes were reported by both concussed and non-concussed athletes and therefore had lower diagnostic value. This finding is supported by other studies which have also found symptoms such as headache to be sensitive for concussion, however not specific if used in isolation without the assistance of other concussion assessment tools.…”
Section: Discussionmentioning
confidence: 98%
“…Current literature is predominantly focused on male collision sports with less research performed on female athletes and non-contact sports. [10][11][12][13] The aim of this study is to retrospectively review SCAT data from concussed and non-concussed elite cricket athletes following a head impact to describe which clinical features on the day of injury are associated with concussion diagnosis. A secondary aim is to describe the typical recovery time of concussed athletes including symptom resolution and RTP.…”
Section: Introductionmentioning
confidence: 99%
“…7 In view of this, a recent study in professional hockey players examining the diagnostic utility of the SCAT-5 within the first 24 hours of injury found a significant decline in performance of both immediate and delayed recall 10-word list tests. 13 However, other studies that have evaluated the 10-word list test in athletes have been limited to healthy samples. [14][15][16] Thus, it is still unknown whether there is utility in the 10-word list test for discriminating concussed from healthy athletes beyond professional hockey and whether differences exist between male and female athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Concussion diagnosis is complex in that it requires synthesis of multifactorial, non-specific clinical information [7]. The diagnostic decision making in standard clinical practice is complicated by factors such as varying symptom assessment tools; unclear thresholds for diagnosis; heterogeneous and non-specific symptom presentations that may also be observed among patients with other injuries, chronic pain, or psychiatric conditions; and an absence of definitive diagnostic biomarkers [8][9][10]. The SCAT tools provide an evidence-based, uniform and standardized assessment of concussion, to assist health professionals with the clinical diagnosis of concussion.…”
Section: Introductionmentioning
confidence: 99%